(untitled) (Bangladesh Journal of Botany, 2019)
The aim of this study was optimization of pectinolytic enzymes i.e. pectin methylesterase and polygalacturonase from Schizophyllum commune using the mosambi peels as substrate in a solid state fermentation process. Results revealed that maximum pectin methylesterase activity of 394.82 U/ml was observed at pH 6, temperature 35°C, time period of 3 days, substrate concentration of 3 g and 3 ml inoculum size. While polygalacturonase showed maximum activity of 381.69 U/ml at pH 4, temperature 45°C, time period of 1 day, substrate concentration 25 g and 5 ml inoculum size. Statistical analysis revealed that the proposed model was found very significant as indicated by p-values.